2016
DOI: 10.1371/journal.pone.0155303
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Assessment of Cerebral Perfusion during Cardiac Arrest, Extracorporeal Life Support and Cardiopulmonary Resuscitation in Rats – A Pilot Trial

Abstract: Cerebral metabolic alterations during cardiac arrest, cardiopulmonary resuscitation (CPR) and extracorporeal cardiopulmonary life support (ECLS) are poorly explored. Markers are needed for a more personalized resuscitation and post—resuscitation care. Aim of this study was to investigate early metabolic changes in the hippocampal CA1 region during ventricular fibrillation cardiac arrest (VF-CA) and ECLS versus conventional CPR. Male Sprague-Dawley rats (350g) underwent 8min untreated VF-CA followed by ECLS (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Excessive neuronal depolarization after a brain injury results in intracellular Ca 2+ overload and sustained glutamate release (excitotoxicity) (Chamoun et al , 2010 ; Schober et al , 2016 ). Moreover, extracellular glutamate levels are further increased by pathological reversal of astrocytic glutamate transporters (Gouix et al , 2009 ).…”
Section: Classic Mechanisms Mediating Neuroprotective Hypothermiamentioning
confidence: 99%
“…Excessive neuronal depolarization after a brain injury results in intracellular Ca 2+ overload and sustained glutamate release (excitotoxicity) (Chamoun et al , 2010 ; Schober et al , 2016 ). Moreover, extracellular glutamate levels are further increased by pathological reversal of astrocytic glutamate transporters (Gouix et al , 2009 ).…”
Section: Classic Mechanisms Mediating Neuroprotective Hypothermiamentioning
confidence: 99%
“…LPR had a five-fold increase from baseline levels, and peaked 8 min after return of spontaneous circulation. Glutamate also had a marked increase (3.5-fold) after CA [ 116 ].…”
Section: Microdialysismentioning
confidence: 99%
“…Overall, microdialysis has proven useful in clinical settings to monitor cerebral metabolism in critically ill neurological and neurosurgical patients, enabling physicians to provide more effective treatment depending on which biochemical signals are present [ 117 ]. However, recent studies have demonstrated the growing applications for this tool, used not only for detection of ischemia and distinguishing ischemia from mitochondrial dysfunction, but also detection of successful reperfusion, even comparing different methods of resuscitation [ 116 ]. The growing trend of extended neuromonitoring including devices such as microdialysis is used to gain more personalized information about the patient and their specific brain injury, and thus facilitating the physicians’ decision making in terms of which treatments to pursue [ 118 ].…”
Section: Microdialysismentioning
confidence: 99%
“…Except for Hc, our model revealed absence of histological signs for neurodegeneration or gliosis at this late time point (7,9,74). It has been shown, that the duration and the depth of the ischemic insult affect the chronology of the manifestation of neuronal damage in the different brain regions (75).…”
Section: Discussionmentioning
confidence: 63%